STORIES FROM THE PAST: LIVING ON SUGAR ESTATES IN MAURITIUS - Raniya , Sahil Lutchman (International Journal of Allied Research in Sociology and Anthropology, 2023)
Mauritius, an idyllic island nestled in the South West Indian Ocean, is a unique case in the annals of immigration history. It lacks a native population, with all its inhabitants tracing their roots to various waves of immigration spanning centuries. This paper delves into the historical narratives that have shaped Mauritius’ multicultural landscape. The island’s history is characterized by three significant waves of immigration – Dutch, French, and British. Notably, the British colonial era was pivotal in shaping the demographic composition of the island. With the advent of sugarcane as a highly profitable industry, the demand for labor surged. Slavery had been abolished in 1835, prompting the British authorities to seek alternative sources of labor. This need led to the recruitment of indentured laborers from India, primarily hailing from North India, to support the burgeoning sugarcane industry. These indentured laborers, in accordance with the terms of their contracts, received essential amenities like a standard of living, wages, ration, housing, and medical care. This paper specifically focuses on the Great Experiment initiated by the British Imperial Government, which involved the recruitment of indentured laborers to work in Mauritius. The indentured laborers, coming from India, marked the beginning of a new chapter in the island’s history. The Hunter-Arbuthnot and Company holds the distinction of bringing the first batch of these immigrants to Mauritius on the ship Atlas, on November 4, 1834. These individuals were subsequently sent to the remote village of Antoinette Phooliar, situated in Belle Alliance, within the Riviere du Rempart district. In Antoinette Phooliar, they worked side by side with a cadre of two hundred slaves in the sugarcane fields, laying the foundation for the island’s economic transformation. This historical exploration of immigration in Mauritius sheds light on the island’s unique social fabric, influenced by waves of immigrants who arrived under varying circumstances. By examining the shifts in immigration patterns and labor systems, this research contributes to a comprehensive understanding of the multicultural dynamics that have evolved over the centuries, and the enduring impact of these historical events on modern Mauritius